44.8k views
5 votes
what is the simplified form of the following expression? Assume x is greater than or equal to 0 and y is greater than or equal to 0. 2(4sq root16x)-2(4sq root 2y)+34 sq root 81x)-4(4sq root32y)

User Sarvesh
by
6.1k points

2 Answers

1 vote

Answer:


338√(x) -72√(2y)

Explanation:

The expression is


2(4√(16x))-2(4√(2y)+34 √(81x)-4(4√(32y) )

Where
x\geq 0 and
y\geq 0

First, we use distributive property


8√(16x)-8√(2y)+34√(81x)-16√(32y)

Then, we simplify square roots


8(4)√(x) -8√(2y)+34(9)√(x) -16(4)√(2y)

Now, we multiply and group similar roots


32√(x) -8√(2y) +306√(x) -64√(2y) \\(32+306)√(x) +(-8-64√(2y) )\\338√(x) -72√(2y)

Therefore, the simpliest form of the given expression is


338√(x) -72√(2y)

User Gmsi
by
5.3k points
3 votes

the given expression is :

2(4√16x) - 2(4√2y) + 34√81x - 4(4√32y)

⇒ 8(√16x) - 8(√2y) + 34√81x - 16√32y

8×4√x - 8√2y + 34×9√x - 16√16×2y [∵ √16 = 4 and √81 = 9]

⇒32√x - 8√2y + 306√x - 16×4√2y

⇒(32√x + 306√x) - 8√2y - 16×4√2y

⇒338√x -72√2y

User Adedoyin Akande
by
5.8k points